Sade's Philosophical System in its Enlightenment Context - Lloyd, Henry Martyn (Springer International Publishing, 2018)
This book connects the philosophy of the Marquis de Sade-one of the most notorious, iconic, and yet poorly-understood figures within the history of European thought-with the broader themes of the Enlightenment. Rather than seeing himself as a mere pornographer, Sade understood himself as continuing the progressive tradition of French Enlightenment philosophy. Sade aspired to be a philosophe. This book uses intellectual history and the history of philosophy to reconstruct Sade's philosophical 'system' and its historical context. Within the period's discourse of sensibility Sade draws on the philosophical and the literary to form a relatively sophisticated 'system' which he deploys to critically engage with the two major strands of eighteenth-century ethical theory: the moral sense and natural law traditions. This work is of interest to: 'Continental' Philosophy, Critical Theory, French Studies, the History of Eighteenth-Century Philosophy, Literary Studies, the History of Moral Philosophy, and Enlightenment Studies. .